2015
DOI: 10.1177/1748895815572163
|View full text |Cite
|
Sign up to set email alerts
|

Precarious identities: ‘Young’ motherhood, desistance and stigma

Abstract: This article explores desistance from crime and experiences of stigma amongst 19 young mothers with a criminal past. Drawing on narrative interview data from a qualitative longitudinal study of women criminalised as children, I argue that young mothers with a history of lawbreaking, as well as other markers of a spoiled past, are likely to encounter intense forms of gendered surveillance, social censure and stigma across multiple domains of identity, regardless of whether or not they are currently involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 39 publications
4
72
0
Order By: Relevance
“…Not explain everything, nor explain with perfect precision, but does it seem to hold promise for the field? Our study supports other emerging studies in the literature both qualitative [12,38,51,60,64] and quantitative [43,57] which point to the fact that one's identity (and identity change) is related to desistance.…”
Section: Resultssupporting
confidence: 80%
“…Not explain everything, nor explain with perfect precision, but does it seem to hold promise for the field? Our study supports other emerging studies in the literature both qualitative [12,38,51,60,64] and quantitative [43,57] which point to the fact that one's identity (and identity change) is related to desistance.…”
Section: Resultssupporting
confidence: 80%
“…Unfortunately, although both discuss the importance of human agency in desistance, there is an unreconciled tension and discrepancy between the main theoretical account of desistance and the role played by human agency. Recent empirical work that relies on the voices of offenders themselves, however, is illuminating the explanatory gaps in these theories [12,59,70,73]. As such, it would appear that the time has come for theoretical reflection within the discipline.…”
Section: Introductionmentioning
confidence: 94%
“…Jennifer also indicated that she had constructed a positive "positive self" and a roadmap to get there: "… now I realized I have to finish my schooling, I have to get a job". Sharpe [70] conducted in-depth interviews with 19 mothers with a non-trivial history of criminal offending. These women revealed how difficult it was for serious offenders to link with good, well-paying jobs and to a person they expressed in vivid terms the stigma they felt they faced in turning their lives around.…”
Section: Recent Empirical Studies Of Desistance: Marriage Employmentmentioning
confidence: 99%
“…Breen [20] also reported that these desisting women in her sample changed their preferences as well as their identities and adopted more prosocial values. Similar research was conducted by Sharpe [109], who interviewed 19 mothers, each with nontrivial offending histories. These women revealed how difficult it was for serious offenders to secure well-paying jobs and they vividly expressed the stigma that they perceived while attempting to turn their lives around.…”
Section: Introductionmentioning
confidence: 92%